2016
DOI: 10.3391/mbi.2016.7.4.11
|View full text |Cite
|
Sign up to set email alerts
|

The ability of scent detection canines to detect the presence of quagga mussel (Dreissena rostriformis bugensis) veligers

Abstract: The expansion of invasive non-indigenous species in the Mediterranean is generating an increasing concern about biodiversity protection and human health, with European countries being solicited to apply early warning measures in such circumstances. The recent expansion of the hazardous fish Lagocephalus sceleratus in the Straits of Sicily, the subsequent actions adopted to manage the risk and the feedback received from the public are herein presented, as an example of the interaction between experts and the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Un altro punto importante da tenere in considerazione è quali fattori aumentano il livello di fatica del cane e, di conseguenza, diminuiscono la sua affidabilità (DeShon et al 2016). Ad esempio, alberi lontani l'uno dall'altro, sottobosco molto denso, terreno ripido e temperature elevate o piogge estive possono costringere la coppia cane-conduttore a lavorare in condizioni non certo ottimali.…”
Section: Discussioneunclassified
“…Un altro punto importante da tenere in considerazione è quali fattori aumentano il livello di fatica del cane e, di conseguenza, diminuiscono la sua affidabilità (DeShon et al 2016). Ad esempio, alberi lontani l'uno dall'altro, sottobosco molto denso, terreno ripido e temperature elevate o piogge estive possono costringere la coppia cane-conduttore a lavorare in condizioni non certo ottimali.…”
Section: Discussioneunclassified
“…Faecal sample collection rates were four times higher using dogs than opportunistic methods. DeShon et al (2016) demonstrated that under controlled laboratory conditions, dogs could detect larvae of the invasive quagga mussel (Dreissena rostriformis bugensis) at concentrations similar to those found in natural aquatic systems. Given dogs' ability to detect a wide variety of target scents, including highly cryptic species, they could also be used to detect incursions of invasive fish in water samples retrieved from the field.…”
Section: Introductionmentioning
confidence: 95%
“…DeShon et al 2016). For example, trees can be distant from each other, the vegetation can be impervious and scheduled searches might need to be conducted under sub-optimum weather conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%